The Impact of Tourism Marketing on Visitor Interest in Cikadongdong River Tubing, Majalengka, West Java - RD Rita Ritasari; Mita Purnamasari; Ria Aryani; Debi Widianingsih (The Postgraduate School of Tourism Sahid Polytechnic, 2024)
Purpose: This study aims to determine whether and how much tourism marketing influences interest in visiting Cikadongdong River Tubing Majalengka, West Java. Research Methods: This research uses quantitative methods. The data collection technique used a questionnaire, and the analysis unit amounted to 100 respondents. The sample used is non-probability, namely purposive sampling. The analysis method used is simple regression analysis. Data testing uses validity and reliability tests, followed by classical assumption tests, namely normality test and heteroscedasticity test, hypothesis testing, and determinant test, using SPSS 20 as a data processing tool. Result and Discussion: The results of this study indicate that tourism marketing significantly affects visiting interest. The t-value of the tourism marketing variable is 13.436, while the t-table value is 1.984, confirming that tourism marketing (X) influences visiting interest (Y). The coefficient of determination (R Square) shows that tourism marketing explains 64.8% of the variation in visiting interest. This indicates that marketing efforts significantly contribute to the decision to visit Cikadongdong River Tubing, while 35.2% of the variance is due to other factors not examined in this study. Implication: The results of this study indicate that tourism marketing has a significant effect on visiting interest. This can be proven by the t value of the tourism marketing variable being 13.436 and the t table value being 1.984. Ha can be accepted if the t value is 13.436> t table 1.98477. It can be stated that the tourism marketing variable (X) affects visiting interest (Y) by 64.8% or 0.648 R Square.